Towards a Typology of Negation in South Asian Languages - Peterson, John; Chevallier, Lennart (Bhasha, 2022)
The present study is a preliminary typology of negation in South Asian languages, based on a database of 25 structural features for 39 languages from three language families and two language isolates. The documented features include the form of the negative marker, the relation of the negative construction to the corresponding affirmative form, whether there are different negative constructions used in different TAM categories, and whether these constructions are symmetric or asymmetric. This study also provides a first analysis of the distribution of these different negative-marking strategies throughout the subcontinent and suggests that a combination of both family bias and areal pressure are needed to account for many of the observed distributions. In some cases of language contact, the data also allows us to determine with some certainty the type of contact situation which has led to the negative-marking patterns documented in the database.